The view from the outside : Nicolas Gervaise, Simon de la Loubere and the perception of seventeenth century Siamese government and society - Trakulhun, Sven (My University, 1997)
This analysis examines the accounts of two European seventeenth century authors, Nicolas Gervaise and Simon de La Loubere, against the background of European modes of interpretation. Hitherto, European sources for Siam were mainly used to reconstruct historical facts. However, this has specific difficulties. Being a part of a literary genre, the composition of travel accounts did not depend on individual observations alone but also on the methods being used to present distant civilisations and exotic cultures to a European public. This study focuses on the detection of conventions and categories of judgement which were developed in West European discourse. The writings of Nicolas Gervaise and Simon de La Loubere are perfect examples to illuminate the nature ofEurocentric attitudes toward the observed society.
Keywords: 900